The Environmental and social impact of the San Mateo sanitary landfill : a study - Opong, Rourie Belonio (Manila : National University, 2007)
The study focused on the San Mateo Sanitary Landfill located in the boundary of San Mateo town and Antipolo City. The aspect of the landfill that were looked into by the researcher included its effect on the environment and the community, problems encountered, and solutions recommended to solve the problems.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.